A flexible energy harvester based on a lead-free and piezoelectric BCTZ nanoparticle–polymer composite. Issue 40 (3rd October 2016) - Baek, Changyeon; Yun, Jong Hyuk; Wang, Ji Eun; Jeong, Chang Kyu; Lee, Keon Jae; Park, Kwi-Il; Kim, Do Kyung
Abstract : A lead-free and piezoelectric BCTZ nanoparticle-based flexible energy harvester generates high-output energy sources from biomechanical motions. Abstract : Lead-free piezoelectric 0.5(Ba0.7 Ca0.3 )TiO3 –0.5Ba(Zr0.2 Ti0.8 )O3 (BCTZ) nanoparticles (NPs) composed of earth-abundant elements were adopted for use in a flexible composite-based piezoelectric energy harvester (PEH) that can convert mechanical deformation into electrical energy. The solid-state synthesized BCTZ NPs and silver nanowires (Ag NWs) chosen to reduce the toxicity of the filler materials were blended with a polydimethylsiloxane (PDMS) matrix to produce a piezoelectric nanocomposite (p-NC). The naturally flexible polymer-based p-NC layers were sandwiched between two conductive polyethylene terephthalate plastic substrates to achieve a flexible energy harvester. The BCTZ NP-based PEH effectively generated an output voltage peak of ∼15 V and a current signal of ∼0.8 μA without time-dependent degradation. This output was adequate to operate a liquid crystal display (LCD) and to turn on six blue light emitting diodes (LEDs).